A Parametric Study of Piled Raft Foundation in Clay Subjected to Concentrated Loading - Chong, Yi Hong; Lee, Min Lee; Kok, Sien Ti; Wong, Soon Yee (International Journal of Integrated Engineering, 2021)
The use of piled raft foundation in building and infrastructure constructions is increasingly popular because of its effectiveness in reducing overall and differential settlements. Parameters influencing the performance of the piled raft foundation need to be comprehended in order to optimize the design of the piled raft system. Most of the current available literature focused on the piled raft foundation subjected to a uniform distributed load in sandy material. This parametric study aims to provide insights into the performance of the piled raft foundations subjected to concentrated loading in clay. A series of 2D finite element analyses were performed to investigate the influencing parameters affecting the load distribution and settlement behaviour of the piled raft. The results suggested that increases in both pile length and raft thickness, as well as a decrease in pile spacing would reduce the differential settlement of the piled raft. Comparatively, raft thickness was the most significant controlling parameter affecting the differential settlement. The study also revealed the importance of placing the pile nearer to the location of concentrated load as it would yield a more uniform load distribution, and hence a lower differential settlement.